Knowledge, attitude and practice of medical personnel on smoking cessation guidelines: a review on associations and questionnaires - Shalihin, Mohd Shaiful Ehsan; Md Aris, Mohd Aznan; Nik Mohamed, Mohamad Haniki; Mohd Rus, Razman; Jamani, Nurjasmine Aida (2015)
Number of active smokers in Malaysia is increasing despite availability of stop smoking clinics and smoking cessation medications. Other than smokers’ level of motivation to quit smoking, competency of the healthcare professionals involved in providing smoking cessation intervention using evidence-based guidelines needs to considered. Hence, knowledge, attitude and practice (KAP) of the healthcare providers in relation to existing clinical practice guidelines on smoking cessation should be assessed. In this review, we look at the previous available questionnaire, for the purpose of applying it to the context of the Malaysian healthcare providers.